PENGARUH PROGRAM KESELAMATAN & KESEHATAN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. INECDA KABUPATEN INDRAGIRI HULU - Yulio Nanda Gunawan; Marnis '; Nuryanti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted at PT. Inecda Indragiri Hulu, this study aimed to determine the effect of variables Health and Safety at Work and Motivation simultaneously and partially on the productivity of employees of PT. PT. Inecda Indragiri Hulu. The sampling method using census method with a total sample of 64 people. Data collection methods used were interviews directly to parties - parties involved with the issues that are being discussed and gave questionnaires to employees in accordance with the research conducted. Data were analyzed using Method Qualitative and Quantitative Methods that use a formula that Descriptive Statistics, Data Quality Test, Multiple Linear Regression Analysis and Testing Hypotheses, with SPSS (Statistical Product and Service Solutions). The results showed that simultaneous Occupational Safety and Health Program of Work and Work Motivation significant effect on the productivity of employees working at PT. Inecda Indragiri Hulu, partially variable Occupational Safety and Health Program of work and motivation significant effect on the productivity of employees of PT. Inecda Indragiri Hulu. regression coefficient is positive (+) indicates a unidirectional relationship, in other words the Occupational Safety and Health Program crimes and motivation will increase the productivity of employees working at PT. Inecda Indragiri Hulu. Correlation or relationship between the Occupational Safety and Health Program of work and work motivation denganProduktivitas Employees working at PT. Inecda Indragiri Hulu is strongly at (r = 0.818) and the coefficient of determination or the number of R-square is equal to 0.669.Keywords: Health, Safety, Work, Motivation, and Productivity